2007
DOI: 10.1007/s00228-007-0404-3
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of metoprolol metabolism and potentiation of its effects by paroxetine in routinely treated patients with acute myocardial infarction (AMI)

Abstract: A pronounced inhibition of metoprolol metabolism by paroxetine was observed in AMI patients, but without serious adverse effects. We suggest, however, that the metoprolol dose is controlled upon initiation and withdrawal of paroxetine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 38 publications
1
40
0
5
Order By: Relevance
“…Totalt ble åtte studier/rapporter som belyser interaksjonsrisiko mellom metoprolol og antidepressiver identifisert (4)(5)(6)(7)(8)(9)(10)(11). Tabell 1 oppsummerer hovedfunn fra disse publikasjonene.…”
Section: Resultaterunclassified
See 1 more Smart Citation
“…Totalt ble åtte studier/rapporter som belyser interaksjonsrisiko mellom metoprolol og antidepressiver identifisert (4)(5)(6)(7)(8)(9)(10)(11). Tabell 1 oppsummerer hovedfunn fra disse publikasjonene.…”
Section: Resultaterunclassified
“…Blant annet ble treningsindusert pulsøkning redusert med 30-40 % i kombinasjon med paroksetin (4). Interaksjonen mellom metoprolol og paroksetin er senere blitt bekreftet i en studie på hjertepasienter, der plasmakonsentrasjonen av metoprolol økte drøyt fire ganger (5 (6). Denne studien viste at økningen i plasmakonsentrasjonen av metoprolol var noe mindre ved bruk av depotformulering sammenliknet med vanlig tablettformulering, men økningen var også kraftig med depotformuleringen -i stør-relsesorden 3-4 ganger (6).…”
Section: Resultaterunclassified
“…It was reported that concurrent use of CYP2D6 substrates or inhibitors could influence cardiovascular patients’ therapeutic responses, in some cases even result in adverse effects. For example, when acute myocardial infarction patients were treated with metoprolol (a substrate for CYP2D6) and co-treated with paroxetine (an inhibitor of CYP2D6), paroxetine inhibited the metabolism of metoprolol and increased its concentration maximum (Cmax), resulting in enhanced therapeutic effects and/or adverse effects, such as severe dizziness, fainting and heart failure [34]. In anti-cancer therapy, many studies have demonstrated that altered expression of DMEs can influence the sensitivity and toxicity of drugs in target cells, and the expression of DMEs plays a pivotal role in chemotherapy sensitivity, resistance, and/or carcinogenesis [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Most patients treated for depression in primary care are treated with antidepressants [43], and common side effects include diarrhea, dizziness, dry mouth, fatigue, headache, nausea, sexual dysfunction, excessive sweating, tremors and weight gain [44]. Less common but potentially more serious adverse effects, particularly for patients in primary care with heart disease, may include increased risk of bleeding and unwanted effects on blood pressure and heart rate [45-49], as well as drug-drug interactions with cardiac medications [50,51]. For patients with generally low levels of depression, who are most likely to be newly identified through screening, the side effect burden and potential risk profile of antidepressants need to be carefully considered, particularly given that screening has not been shown to reduce symptoms of depression.…”
Section: Discussionmentioning
confidence: 99%